2014
DOI: 10.1136/jnnp-2014-307719
|View full text |Cite
|
Sign up to set email alerts
|

APOE genotype and neuroimaging markers of Alzheimer's disease: systematic review and meta-analysis

Abstract: Objective We aimed to examine the association of apolipoprotein E (APOE) ε4 genotype with neuroimaging markers of Alzheimer’s disease: hippocampal volume, brain amyloid deposition and cerebral metabolism. Methods We performed a systematic review and meta-analysis of 14 cross-sectional studies identified in Pubmed from 1996 to 2014 (n=1628). The pooled standard mean difference (SMD) was used to estimate the association between APOE and hippocampal volume and amyloid deposition. Meta-analysis was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 40 publications
(50 reference statements)
3
98
1
Order By: Relevance
“…The APOE e4 allele has been shown to increase risk for developing AD in both the DS (Coppus et al, 2008;Prasher et al, 2008;Rohn et al, 2014) and TD populations (Bertram and Tanzi, 2008;Corder et al, 1993;Liu et al, 2015). The observed e4 carrier frequency was 5 out of 54 alleles, or 9%, which is similar to the frequency observed in the general population (13%) (Bertram and Tanzi, 2008;Corder et al, 1993;Liu et al, 2015).…”
Section: Exploratory Analyses In Dsmentioning
confidence: 54%
“…The APOE e4 allele has been shown to increase risk for developing AD in both the DS (Coppus et al, 2008;Prasher et al, 2008;Rohn et al, 2014) and TD populations (Bertram and Tanzi, 2008;Corder et al, 1993;Liu et al, 2015). The observed e4 carrier frequency was 5 out of 54 alleles, or 9%, which is similar to the frequency observed in the general population (13%) (Bertram and Tanzi, 2008;Corder et al, 1993;Liu et al, 2015).…”
Section: Exploratory Analyses In Dsmentioning
confidence: 54%
“…However, this study described higher baseline CBF in ApoE4 carriers at baseline, which we only observed in the anterior cingulate cortex. A recent meta-analysis 48 identified the right middle frontal gyrus, the region which is most consistently identified to be hypometabolic in FDG-PET studies. This region also showed reduced CBF in our analysis.…”
Section: Influence Of Apoe and Pib On Cbfmentioning
confidence: 99%
“…[1][2][3] The inverse relationship between fibrillar b-amyloid plaque load and regional glucose metabolism is particularly intriguing, [4][5][6] and recent studies have interrogated the complex relationship between b-amyloid, metabolism, and genotype.…”
Section: Introductionmentioning
confidence: 99%